Faktor-Faktor Keterbengkalaian Benteng Toboali Sebagai Bangunan Bersejarah - Sutanto, Ari (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
Buildings and areas that have historical significance should essentially be seen as an object of cultural heritage that needs to be protected and preserved. Cultural significance in Fort Toboali also affects its condition now abandoned so this research aim to determine the factors that influence the abandonment of Toboali Fort as a historical building by cultural significance. This research uses quantitative deductive rationalistic through questionnaires distributed to respondents consisting of government and the people living around Toboali Fort to find the cultural significance of Fort Toboali and performed statistical analysis using factor analysis with SPSS 17 so that the newly discovered factors that influence the abandonment of Toboali Fort as historical building. Based on factor analysis , found 4 factors that influence the neglligence of Toboali Fort as a historical building that is 1) function, 2) aesthetic, 3) preservation supporting and 4) historical factor, the main factor is the factor function that gives the biggest influence (34,99%). Reseach finding of this study supports the theory that is used, namely the neglect of cultural significance lead to the abandonment of a historical building, but the abandonment of Toboali Fort more affected by the neglect of scientific, social, economic value and adapted reuse thatÂ refer to Function Factor of Toboali Fort.